2020
DOI: 10.2147/ott.s229835
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dynamic Changes in Serum Markers and Their Utility in the Early Diagnosis of All Stages of Hepatitis B-Associated Hepatocellular Carcinoma</p>

Abstract: Objective: This study aimed to evaluate the individual and combined diagnostic values of serum alpha-fetoprotein (AFP), des-gamma-carboxyprothrombin (DCP), glypican-3 (GPC3) and golgi protein 73 (GP73) in diagnosing hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Methods: Participants from Beijing YouAn Hospital were enrolled and divided into seven groups. Serum was collected and the levels of AFP, GPC3, GP73 and DCP were simultaneously measured with a protein array. Pearson's χ 2 test was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Moreover, we did not manage to detect any benefit regarding the efficacy of GP73 at early detection of HCC, although GP73 levels were positively associated with BCLC stage and the tumor dimensions. Our findings are in accordance with a recent study from China which showed that AFP remained the best biomarker for the very early diagnosis of HBV-associated HCC, and the combination of one or more markers including GP73 did not significantly improve the diagnostic accuracy for HCC[ 42 ]. In this context, multiple studies have investigated the utility of GP73 for detecting HCC with conflicting results[ 13 , 33 , 43 - 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we did not manage to detect any benefit regarding the efficacy of GP73 at early detection of HCC, although GP73 levels were positively associated with BCLC stage and the tumor dimensions. Our findings are in accordance with a recent study from China which showed that AFP remained the best biomarker for the very early diagnosis of HBV-associated HCC, and the combination of one or more markers including GP73 did not significantly improve the diagnostic accuracy for HCC[ 42 ]. In this context, multiple studies have investigated the utility of GP73 for detecting HCC with conflicting results[ 13 , 33 , 43 - 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many recent studies evaluated individual and combined diagnostic values of serum alpha-fetoprotein (AFP), des-gamma-carboxyprothrombin (DCP), glypican-3 (GPC3) and golgi protein 73 (GP73) in diagnosing HCC. [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] One study by Li et al showed combination of serum levels of miR-122, GPC3 and AFP improved power of HCC detection. 66 Several studies showed that the sensitivity of circulating GPC3 is superior to AFP for detecting HCC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GPC-3 showed only a moderate diagnostic accuracy. Previous reports showed contradictory results concerning the accuracy of GPC-3 for the detection of HCC [17,[29][30][31]; as a matter of fact, the control population included in the studies (i.e., patients with cirrhosis or chronic liver disease or healthy subjects), the overall clinical and biochemical characteristics of the patients enrolled, the different assays used for the measurement of GPC-3 may have accounted for these conflicting findings.…”
Section: Discussionmentioning
confidence: 99%